Որոշ դիտողություններ նկարազարդ ձեռագիր «Շահնամե»-ի վերաբերյալ - Թաջարյան, Իվեթ («Նաիրի» հրատ.)
Уникальным явлением в искусстве Каджарского периода в Иране (XIX в.) является иллюстрированная рукопись “Шахнаме” № 535 из арабографического фонда Матенадарана. Нами установлено, что рукопись имеет 56 иллюстрированных страниц (прежние исследователи называли другие цифры). Исследование позволяет заключить, что над рукописью работали несколько миниатюристов и два писца. В колофоне указано имя одного писца, а об иллюстраторе упоминаний нет. В статье рассматривается уникальная миниатюра “Рустам убивает белого дьявола”, иконография которой, как нам удалось определить, отклоняется от известного канонического типа рукописных иллюстрированных “Шахнаме”. Matenadaran‟s illuminated Shahnameh manuscript (ms. 535 of the Arabic Script Manuscript Collection) is a unique manifestation of the 19th century Qajar period art in Iran. The manuscript has 56 illuminated pages (former researchers have mentioned different numbers). The study leads to the conclusion that several miniaturists and two calligraphers worked on the manuscript. Only one scribe is mentioned in the colophon, and there is no information about the miniaturists. The paper is devoted to the analysis of a unique miniature, Rustam Killing the White Devil, which deviates from the known types of illustrations of Shahnameh. These peculiarities have not been studied by previous scholars.
Keywords: Մանրանկարչություն; Ձեռագրեր